pH as analytical indicator for managing pork meat quality - Kim, Tae Wan; Kim, Chul Wook; Kwon, Seul Gi; Hwang, Jung Hye; Park, Da Hye; Kang, Deok Gyeong; Ha, Jeongim; Yang, Mi Ra; Kim, Sam Woong; Kim, Il-Suk (Penerbit Universiti Kebangsaan Malaysia, 2016)
In order to examine differences of meat quality traits depending on pH values post-mortem, the pH range was classified according to initial pH (pH45min) and ultimate pH (pH24hr) post-mortem. The differences of meat quality traits depending on sex were not changed by a number of amount, except for backfat thickness and fat content. The value of pH45min was positively correlated with pHdif, whereas pH24hr was negatively associated with lightness (CIE L*) and protein content. At pH45min post-slaughter, collagen content, fat content, shear force, water holding capacity and yellowness (CIE b*) showed lower values at the higher pH range of pH>6.7 than those of other ranges, but CIE L* and redness (CIE a*) presented the lowest value at the intermediate pH range of pH6.3~6.7. Conversely, at pH24hr post-slaughter, fat and moisture contents maintained the highest average values at the higher pH range of pH>6.1, but protein content showed higher value at the lower pH range of pH<5.7. Higher pH24hr appeared significantly lower shear force, but higher water holding capacity. CIE L*, a*, and b* values showed significantly higher values at the lowest region of pH24hr. Since meat quality characteristics seemed to be favored by consumers in rather than at the range of pH5.7~6.1, which showed significant differences of meat color, appearance, and meat juiciness, it is suggested that production of pork meat to appropriate pH value is performed by pig breeders and control measures taken during pre- and post-slaughters.